2021
DOI: 10.7759/cureus.15973
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity Secondary to Levofloxacin Use

Abstract: Levofloxacin is a broad-spectrum antibiotic that is used in the treatment of many infections. A rare adverse drug reaction following the use of levofloxacin is drug-induced liver injury. The exact mechanism behind fluoroquinolone-induced liver injury is unknown, but many severe, sometimes fatal hepatotoxicity cases are reported. Current recommendations advise clinicians to discontinue levofloxacin immediately if the patient develops signs and symptoms of hepatitis. This case report presents a 79-year-old male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Although we did not observe a concurrent rise in total bilirubin and alkaline phosphatase, our patient’s baseline characteristics fit the patients described in these case studies. Previous case studies raised other factors affecting liver injury, including impaired renal function and a lack of renally dosing medications; however, our patient’s glomerular filtration rate was >60 mL/min [ 14 ]. Medications may cause hepatotoxicity, although this was a less likely cause for our patient.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although we did not observe a concurrent rise in total bilirubin and alkaline phosphatase, our patient’s baseline characteristics fit the patients described in these case studies. Previous case studies raised other factors affecting liver injury, including impaired renal function and a lack of renally dosing medications; however, our patient’s glomerular filtration rate was >60 mL/min [ 14 ]. Medications may cause hepatotoxicity, although this was a less likely cause for our patient.…”
Section: Discussionmentioning
confidence: 83%
“…LFTs increased more than 10 times the upper limit of normal in most cases and frequently occurred in association with elevated total bilirubin and alkaline phosphatase. Recovery time averaged from one to three weeks after drug discontinuation [ 14 ]. Although we did not observe a concurrent rise in total bilirubin and alkaline phosphatase, our patient’s baseline characteristics fit the patients described in these case studies.…”
Section: Discussionmentioning
confidence: 99%
“…This antibiotic has broad-spectrum activity. 23 It is widely used in urology due to its efficacy and low price. 24 In the current study, significant difference was not found in resistance ratios of levofloxacin due to relocation.…”
Section: Discussionmentioning
confidence: 99%
“…Some common events may include kidney injury, central nervous system disturbances, Q-T interval prolongation, and gastrointestinal tract offense. Rare occurrences include acute tendon rupture, psychosis, cardiotoxicity, and photosensitivity [ 1 ]. Transaminitis may occur as well, with fulminant hepatitis occurring exceptionally rarely.…”
Section: Introductionmentioning
confidence: 99%